Chest radiography in interstitial lung disease: Accuracy and radiological features from a systematic review and meta-analysis - Mustafa Qafesha, Ruaa; Diaa Hindawi, Mahmoud; Elbadry, Menna; Sharabati, Israa; Mashaly, Doaa; Dervis, Muhiddin; Najah, Qasi; Kashbour, Muataz (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: This systematic review aims to summarize and evaluate the diagnostic performance of chest X-ray (CXR) compared with high-resolution computed tomography (HRCT) for detecting interstitial lung disease (ILD). Research question: what is the diagnostic accuracy and radiological finding of CXR in ILD, using HRCT as a gold standard. Study Design and Method: We systematically searched electronic databases to find studies evaluating the diagnostic accuracy of CXR and HRCT for detecting ILD. We used StataMP/17 and R statistical software for the quantitative analysis. Values like pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio with their 95% confidence interval, and the SROC curve was performed. Results: We included a total of 18 studies involving 1917 patients. Compared to HRCT, CXR had sensitivity of 0.62 (95% CI: 0.47–0.74), specificity of 0.90 (95% CI: 0.85 – 0.93), positive likelihood ratio of 5.9 (95% CI 4.5–7.7), negative likelihood ratio of 0.43 (95% CI 0.31, 0.59), diagnostic odds ratio of 14 (95% CI 9 - 21), and area under the ROC curve of 0.88 (95% CI 0.85–0.91). Deek’s plot showed no publication bias (p= 0.44). CXR had lower sensitivity compared with HRCT in detecting specific radiologic findings. Subgroup analysis revealed that a patient sample surpassing 100 indicated significantly higher specificity. Conclusion: Chest radiography exhibits moderate sensitivity and high specificity for detecting ILD when HRCT is regarded as the gold standard test. Although CXR is recommended as an initial diagnostic tool, it should not be solely relied upon for a definitive diagnosis, as it might miss some cases.